Developer Liability for Shophouses In Buildings By Buyers Standing On State-Owned Land Through Building For Turnover (BGS) - Nazmi, Didi (Ekasakti Journal of Law and Justice, 2024)
The government as a regulator continues to encourage infrastructure development based on the interests of the community in order to boost the nation's economy. Development projects carried out by the government are not only funded from the state, but also by inviting the private sector as business entities to collaborate in infrastructure development. Several schemes have been created by the government through a build-to-transfer system (BGS) by providing land for private parties to build a building. The government provides land for development to business or private entities through Building Use Rights (HGB) over Management Rights (HPL). The purpose of obtaining HGB on HPL is to accommodate investment needs and business feasibility on a lease for a period of 30 (thirty) years. However, the building has been built and can be used by the shophouse users who have experienced losses due to the lack of transparency of important information related to the building by the developer (developer). That way, if the management period ends and the shophouse user has been bought, ownership will change to the government, resulting in a dispute between the user who bought it and the building manager. This research is legal research (doctrinal research) with an analytical approach (conceptual approach), legislative approach (statues approach). The research results explain that the developer's legal responsibility for the buyer's losses must be to transfer or release the HGB over the HPL to another developer who meets the requirements. Then, if the developer cannot carry out the transfer, he must make compensation for operational costs and return the purchase proceeds by 50% (percent) as based on Article 1364 of the Civil Code. The legal action that must be taken by the developer is to file a civil lawsuit against the developer for negligence outside the agreement.